A Compound Elastoplastic Model with Hydrostatic Core and Fracturing for Localization of Nonlinear Deformations in Ice During a Low-Speed Impact - Guseva, E. K.; Golubev, V. I.; Epifanov, V. P.; Petrov, I. B. (Numerical analysis and applications, 2025)
— During dynamic loading, ice demonstrates complex nonlinear behavior which depends on many factors including its strain rate. In practical applications, during the low-speed collision, ice exhibits both viscous and brittle properties. To consider the specifics of local ice failure, a compound model is proposed in this paper, which distinguishes a hydrostatic core and an elastoplastic zone in ice, with the material far from the impact area being in an elastic state. Additionally, volumetric cracking is considered. The model is verified by comparing the results of numerical computations and a laboratory experiment with a spherical indenter. The numerical results demonstrate various phenomena observed in the experiments. The simulations reconstruct nonlinear waves, different destruction patterns, and demonstrate the wave nature of fracturing. The deformation curves calculated confirm the possibility of a qualitative description of ice behavior during the main stage of the collision.